2014
DOI: 10.1038/modpathol.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility and limitations of glutamine synthetase and serum amyloid-associated protein immunohistochemistry in the distinction of focal nodular hyperplasia and inflammatory hepatocellular adenoma

Abstract: Inflammatory hepatocellular adenoma can show overlapping histological features with focal nodular hyperplasia, including inflammation, fibrous stroma, and ductular reaction. Expression of serum amyloidassociated protein in inflammatory hepatocellular adenoma and map-like pattern of glutamine synthetase in focal nodular hyperplasia can be helpful in this distinction, but the pitfalls and limitations of these markers have not been established. Morphology and immunohistochemistry were analyzed in 54 inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 25 publications
4
60
0
2
Order By: Relevance
“…Endothelial cells are Calcified Telangiectatic Hyperplastic Nodule Associated With Vascular Malformation  usually negative for CD34 in normal liver sinusoids but they can become positive in vascular flow alterations and neoplasms [14] like it appeared in our case. On the other hand, GS staining pattern in FNH is described as "map-like" because large groups of hepatocytes around the hepatic veins express GS, while GS patterns in HA are highly variable and range from negative to either uniform around the central venules or patchy at the periphery [10,15]. In our patient, the lesion was GS negative, thus excluding FNH and pointing to a possible HA pattern.…”
Section: Discussionmentioning
confidence: 54%
“…Endothelial cells are Calcified Telangiectatic Hyperplastic Nodule Associated With Vascular Malformation  usually negative for CD34 in normal liver sinusoids but they can become positive in vascular flow alterations and neoplasms [14] like it appeared in our case. On the other hand, GS staining pattern in FNH is described as "map-like" because large groups of hepatocytes around the hepatic veins express GS, while GS patterns in HA are highly variable and range from negative to either uniform around the central venules or patchy at the periphery [10,15]. In our patient, the lesion was GS negative, thus excluding FNH and pointing to a possible HA pattern.…”
Section: Discussionmentioning
confidence: 54%
“…The 50% cutoff was chosen on the basis of the results of the study by Bioulac-Sage et al 3 They had described homogeneous and heterogeneous patterns of glutamine synthetase staining within this group, but did not provide the number of cases for each category. In our study, 2 we also observed homogenous and heterogeneous patterns within the diffuse glutamine synthetase staining group and described them as diffuse-strong and diffuse-intermediate staining, respectively; in addition, we also provided number of cases showing these two patterns within the diffuse category.…”
mentioning
confidence: 54%
“…2 This group has done seminal work regarding the immunohistochemical and molecular features of hepatocellular adenoma and focal nodular hyperplasia. We agree with their previously published data, but it appears that some of our immunohistochemical data has not been clearly represented in their commentary.…”
mentioning
confidence: 99%
“…Strong GS expression in the cytoplasm of hepatocytes, with positive cells forming large sheets arranged in an anastomosed geographic or ''maplike'' pattern, is essentially diagnostic of focal nodular hyperplasia (FNH). 126,127 Glutamine synthetase is usually not expressed in hepatocytes around fibrous scars containing arteries and bile ductules. This unique ''maplike'' pattern is seen in virtually all FNH cases, including those that are morphologically uncharacteristic (Figure 6, A).…”
Section: Immunomarkers For Hepatocellular Neoplasmsmentioning
confidence: 99%